Effect of delays in processing on the survival of Mycobacterium avium-M. intracellulare in the isolator blood culture system. - von Reyn, C F (1991)
Concentrations of Mycobacterium avium-M. intracellulare ranging from 10(-1) to 10(3) CFU/ml were added to blood, placed in Isolator tubes, and held at room temperature for intervals ranging from 4 h to 56 days before being processed (centrifugation and culture on Middlebrook 7H10 agar). At all concentrations tested, M. avium-M. intracellulare was recovered after hold times ranging from 4 h to 7 days; the number of final CFU actually increased progressively for hold times of 8 h or more. Hold times of up to 7 days did not increase the time from processing to the first appearance of visible colonies. At an inoculum of 10(2) CFU/ml, M. avium-M. intracellulare was recovered from Isolator tubes processed 56 days after inoculation. Two Isolator blood cultures were drawn from a patient with AIDS; M. avium-M. intracellulare was recovered from the sample processed immediately and from the sample processed after a hold time of 7 days. Since M. avium-M. intracellulare survives for prolonged periods in Isolator tubes, blood cultures may be collected in outpatient settings or in hospitals without mycobacterial culture facilities and shipped to reference laboratories for processing without loss of viability.